Studying of the complexes product of the nerve agent Soman with the Butyrylcholinesterase and Acetylcholinesterase Enzymes (Baghdad Science Journal, 2008)
Cholinesterases are among the most efficient enzymes known. They are divided into two groups: acetylcholinesterase (AChE) involved in the hydrolysis of the neurotransimitter acetylcholine, and butyrylcholinesterase (BChE) of unknown function. Several crystal structures of the former have shown that the active site is located at the bottom of a deep and narrow gorge. Human BChE has attracted attention because it can hydrolyze toxic esters and nerve agents. Here we analyze the complexes of cholinesterase with soman by describing the 3D geometry of the complex, the active site, the changes happened through the inhibition and provide a description for the mechanism of inhibition. Soman undergoes degradation in the active site of the AChE and BChE. We calculate the energy of the products of the degradation reaction and suggest the reaction path.The product of the former reaction bind to serine residue in the active site and forming a stable bond and ends the catalytic function of the enzyme.This study has a useful role in the search of inhibitors to help in the treatment of Alzahimer's disease.